ASSA13-14-9 Efficacy and Safety of Olmesartan and Olmesartan Plus Hydrochlorothiazide Combined with Amlodipine in Chinese Patients with Mild to Moderate Essential Hypertension. (29th April 2013) - Hongwei, Li; Kezhi, Mei; Qi, Hua; Qiuyan, Dai; Xiaoling, Peng; Hong, Ding; Lin, Pi; Zhimin, Jin; Daifu, Zhang; Ke, Lv; Xingui, Guo; Hui, Xu; et al.
Abstract : Objective: To evaluate the efficacy and safety of olmesartan (OLM) and olmesartan plus hydrochlorothiazide (fixed-dose combination of OLM/HCTZ 20 mg/12.5 mg) combined with amlodipine (AML) in Chinese patients with mild to moderate essential hypertension who had insufficient response for AML mono-therapy. Methods: This was an open label, non-comparative, multicenter clinical trial. The patients who had not achieved targeted BP (defined as DBP < 90mmHg, DBP < 80mmHg if DM subjects) after more than 4 weeks of AML mono-therapy (5 mg/day) were enrolled, and administrated combination of OLM (20 mg/day) and AML (5 mg/day). The possible up-titration points were at the end of week 8 and week 12. The subjects who achieved target BP maintained the treatment. If not, the subjects were up-titrated OLM to 40mg/day or changed OLM to OLM/HCTZ. The treatment selections were decided by the investigators. The total treatment duration was 16 weeks. The primary endpoint was the rate of the responders at the end of week 16 which was defined as 10 mmHg, or the mean SBP reduction > 20 mmHg. Results: In the intent-to-treat analysis (n = 409), the rate of the responders at the end of week 4, 8, 12, 16 was 76.3%, 86.3%, 95.4%, 97.1%, respectively. In terms of DM subjects (n = 54), the rate was 88.9% at the end of treatment. The mean changes of blood pressure from baseline in all subjects at week 4, 8, 12 and 16 were as below. Only one SAE (no drug related) was reported during the study period. Conclusions: In Chinese hypertensive patients with insufficient response for AML mono-therapy, OLM and OLM plus HCTZ combined with AML are efficacious in lowering BP and have an acceptable safety and tolerability profile.